Sistem Informasi Inventaris Barang Berbasis Web pada Kelurahan Kotabumi Pasar Lampung Utara - Leni Maryana; Yulina Yulina (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
This research aims to design and implement a Web-Based Goods Inventory Information System at Kotabumi Pasar Village, North Lampung, to address the challenges associated with manual data collection and asset management. The system was developed using the SDLC Waterfall method, with the PHP programming language and MySQL database. It is designed to provide an intuitive interface and robust functionality, including features for adding, editing, deleting, and searching inventory data, as well as generating automatic reports. By automating these processes, the system seeks to improve the efficiency and accuracy of goods inventory management, reducing the risk of human error and increasing transparency in asset tracking. Additionally, the system is expected to enhance the village administration’s ability to monitor and make informed decisions about asset management, ultimately supporting better organizational performance and resource allocation. This study demonstrates the value of adopting digital solutions to modernize administrative tasks in local government settings, fostering more effective and sustainable governance practices.